Performance Appraisal Standardization Of Educational Manpower And Education Management - Pujiarti Pujiarti; Rinintha Parameswari; Suhendar Janamarta (Fakultas Bisnis, 2021)
Performance appraisal is a planned process and must be carried out periodically to measure the success of the education and learning process. The author limits the discussion in this article to the aspects that must be assessed for educators and education personnel. The current problems are the absence of segregation of the assessed aspects, there are not any standardized of scoring system, and determination of benchmarks used in the assessment. The results of the performance assessment lie with the appraiser who assesses the teaching staff and education staff objectively and not subjectively based on the aspects that must be assessed. The success of the education and teaching process lies in the contribution of the teaching and education personnel performance according to predetermined standards.